Hipercolesterolemia infantil: causas y tratamiento - Caicedo Castillo, Paola Estefanía (Machala : Universidad Técnica de Machala, 2021)
Familial Hypercholesterolemia (FH) is a metabolic disorder with an increase in total cholesterol and low-density lipoproteins, which is prevalent worldwide from childhood and can develop with greater risk until adult life. Two types of HF stand out: homozygous and heterozygous, the latter being the most common. This work is a descriptive cross-sectional study that compiled information from various bibliographic sources to establish the relationship between the clinical picture of a child patient and the results of his laboratory tests. This disease is characterized by high levels of cholesterol and LDL in the blood, caused by a mutation in the LDL receptor gene. By confirming this disorder, the appropriate treatment for the patient can be established, the use of statins being highly recommended, accompanied by hygienic-dietary measures, which will affect the quality of life of the patient.
La Hipercolesterolemia Familiar (HF) es un desorden metabólico con aumento de colesterol total y lipoproteínas de baja densidad, que a nivel mundial es prevalente desde la niñez y puede desarrollarse con mayor riesgo hasta la vida adulta. Se destacan dos tipos de HF: homocigota y heterocigota, siendo esta última la más común. Este trabajo es un estudio descriptivo de corte transversal que recopiló información en varias fuentes bibliográficas para establecer la relación entre el cuadro clínico de un paciente infantil y los resultados de sus pruebas de laboratorio. Esta enfermedad se caracteriza por altos niveles de colesterol y LDL en la sangre, causados por una mutación en el gen receptor de LDL. Al confirmar este trastorno, se puede establecer el tratamiento adecuado para el paciente, siendo muy recomendado el uso de estatinas, acompañado de medidas higiénico-dietéticas, que incidirán en la calidad de vida del paciente.
Keywords: COLESTEROL; HIPERCOLESTEROLEMIA FAMILIAR (HF); ESTATINAS